Child labour's working environment and psychological wellbeing: a study in upcountry, Sri Lanka - Begum, Arf (2019)
This study investigated the influence of child labourer's working environment on their psychological wellbeing, in upcountry Sri Lanka. Upcountry children absenting from their school education and working as a child labour. It is influence on their psychological behaviours. The main objective of this study is to identify the influence of child labourer's working environment on the upcountry child labourer's psychological wellbeing. Data collection was carried out within the upcountry and outside of the upcountry in Sri Lanka. The target population was the upcountry child labourer who is between the ages of 6 to 18 years old absent from school and doing fulltime child labour work. The sample size population was selected among the upcountry child labourers using stratified random methods. The sample is made up of child labourers in the upcountry areas as well as outside the upcountry areas namely Colombo, Kandy and Matale. The total number of respondents is 380, with an equal distribution of 190 males and 190 females. The data analysis carried out with SPSS in correlations and multiple linear regression analysis. The study findings revealed that the child labourer's working environment has influence on the child labourer's psychological emotions of anxiety, aggressive depression and anti-social activities. Further, the child labour's working environment is statistically significant with the child labourer's coping ability, interrelations with parents, father, mother, and peers. The child labourer's life interest was statistically significant with the child labour working environment. However, the child labourer's working environment was not statistically significant with the child labour's life satisfaction. The child labourer's psychological wellbeing than 8.2% of the variance explained by the child labourer's working environment. Thus, this result was taken only from the upcountry child labourers. Future researches may consider how part-time child labourers and fulltime child labourers working environment influence on psychological wellbeing.